2006
DOI: 10.1086/507417
|View full text |Cite
|
Sign up to set email alerts
|

A Reverberation‐based Mass for the Central Black Hole in NGC 4151

Abstract: We have undertaken a new ground-based monitoring campaign to improve the estimates of the mass of the central black hole in NGC 4151. We measure the lag time of the broad H line response compared to the optical continuum at 5100 8 and find a lag of 6:6 þ1:1 À0:8 days. We combine our data with the recent reanalysis of UVemission lines by Metzroth and coworkers to calculate a weighted mean of the black hole mass, M BH ¼ (4:57 þ0:57 À0:47 ) ; 10 7 M . The absolute calibration of the black hole mass is based on no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
218
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(235 citation statements)
references
References 39 publications
14
218
1
2
Order By: Relevance
“…The problems of small sample size and relatively larger uncertainties for lower luminosity objects will soon be mitigated by two independent reverberation-mapping campaigns which have been recently carried out at MDM Observatory and at Lick Observatory and targeted the lowluminosity end of the relationship. Preliminary results from the MDM campaign promise to replace several measurements, as was done in the case of NGC 4593 (Denney et al 2006) and NGC 4151 (Bentz et al 2006b) in the 2005 MDM campaign. And preliminary results from the Lick campaign promise to add several new objects to the low-luminosity end of the R BLR -L relationship (e.g., Bentz et al 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The problems of small sample size and relatively larger uncertainties for lower luminosity objects will soon be mitigated by two independent reverberation-mapping campaigns which have been recently carried out at MDM Observatory and at Lick Observatory and targeted the lowluminosity end of the relationship. Preliminary results from the MDM campaign promise to replace several measurements, as was done in the case of NGC 4593 (Denney et al 2006) and NGC 4151 (Bentz et al 2006b) in the 2005 MDM campaign. And preliminary results from the Lick campaign promise to add several new objects to the low-luminosity end of the R BLR -L relationship (e.g., Bentz et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the Kaspi et al (1996) data set has a rather unconstrained time lag that is consistent with zero once the monotonic increase in the continuum and line flux is removed (see Metzroth et al 2006 for a full discussion). Both of these data sets for NGC 4151 have been superseded by the results reported by Bentz et al (2006b), which we include here in their stead.…”
Section: Flux Measurementsmentioning
confidence: 99%
“…It is important to note that the FM values for D+Ea are slightly offset from the predicted curve, since they were generated using a filtered continuum. For a SMBH mass of M BH = 4.57 × 10 7 M ⊙ (Bentz et al 2006), we determined the Eddington luminosity, L Edd = 5.78 × 10 45 erg s −1 . Based on our determination of the 2-10 keV source luminosity (L 2−10keV ), and by assuming a bolometric correction of ∼ 30 (Awaki et al 2001), we calculated the bolometric luminosity for our studied epochs.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed that, the BLR size as measured for a particular emission line such as Hβ λ4861, is closely related to the AGN luminosity in the approximate form R ∝ L 1/2 (the R-L relation; e.g., Kaspi et al 2000;Bentz et al 2006;Shen & Liu 2012). This relation offers the possibility of taking advantage of single-epoch (SE) spectra to determine the SMBH masses (e.g., Vestergaard 2002;McLure & Jarvis 2002;Vestergaard & Peterson 2006).…”
Section: Introductionmentioning
confidence: 99%